„Es war ein schöner Augusttag des Jahres 1913.“ Lufttemperatur und gesellschaftliche Umbruchssituation in Robert Musils „Der Mann ohne Eigenschaften” - von Hoff, Dagmar (Studia Germanica Posnaniensia, 2015)
In Robert Musil’s fragmentary novel, The Man Without Qualities, history and poetics connect in a very potent manner. A salient example of this is the famous sentence, “It was a fine day in August 1913”, where societal upheaval is portrayed. Meteorological information contrasts and corresponds with scien-tific facts and documented historical events. Above all, it is Musil’s ironic style which brings the text’s literary power of commentary to the fore.